Pharmacokinetics, Tissue Distribution, and Human Serum Albumin Binding Properties of Delicaflavone, a Novel Anti-Tumor Candidate - Chen, Bing; Luo, Hongbin; Chen, Weiying; Huang, Qishu; Zheng, Kaifan; Xu, Dafen; Li, Shaoguang; Liu, Ailin; Huang, Liying; Zheng, Yanjie; Lin, Xinhua; Yao, Hong (Frontiers in Pharmacology, 2021)
Delicaflavone (DF), a natural active ingredient from Selaginella doederleinii Hieron, has been reported to have favourable anticancer effects and is thus considered a potential anticancer agent. However, its pharmacokinetics and plasma protein binding properties remain unknown. Here, we investigated the pharmacokinetic profile of DF in rats using a validated HPLC-MS/MS methods, as well as its human serum albumin (HSA) binding properties through multi-spectroscopic and in silico methods. The results showed that DF was rapidly eliminated and had a widespread tissue distribution after intravenous administration. DF showed linear dynamics in the dose range of 30–60 mg/kg and poor oral bioavailability. The major distribution tissues of DF were the liver, lungs, and kidneys. Ultraviolet and fluorescence spectroscopy and molecular docking demonstrated that DF had a static quenching effect on HSA, with one binding site, and relatively strong binding constants. Thermodynamic analysis of the binding data revealed that hydrogen bonding and van der Waals interactions played major roles in binding. The results of this study further our understanding of the pharmacokinetic and plasma protein binding properties of the potential anticancer agent DF and shed light on pharmacological strategies that may be useful for the development of novel cancer therapeutics.